The challenge of detecting prey: Private and social information use in predatory bats. (23rd September 2019) - Page, Rachel A.; Bernal, Ximena E.
Abstract: In the evolutionary arms race between predators and their prey, prey often evolve to be as cryptic as they can, while predators in turn hone their sensory strategies to detect prey. Examinations of the sensory strategies implemented by predators to detect their prey, as well as the ecological consequences of these interactions, are at the crux of understanding and predicting predator–prey dynamics. We review the sensory strategies used by predators that rely on private information (attending directly to cues and signals generated by their prey) and those that gather social information (attending to the signals and behaviours of others). We focus our enquiry on bats, an ideal group to shed light on these questions given their ecological diversity, varied foraging strategies and wide range of social behaviours. We discuss the costs and benefits of using private and social information for foraging. We investigate diverse strategies of information use and examine the effects different predatory strategies have on predator sensory systems. We provide an overview of the sensory ecology of information use in hunting in bats and, by identifying current gaps in knowledge, highlight fruitful directions for future research. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.